A case of successful transarterial stenting for pseudoaneurysm after pancreaticoduodenectomy. Issue 4 (30th April 2020) - Kitamura, Fumimasa; Okabe, Hirohisa; Yamashita, Yo‐ichi; Miyata, Tatsunori; Hayashi, Hiromitsu; Imai, Katsunori; Chikamoto, Akira; Baba, Hideo
Abstract: Postpancreaticoduodenectomy (PD) bleeding, which is reported to occur in 5–7%, is a major complication that often causes life‐threatening secondary events. A transarterial catheter technique with coil embolization is a widespread procedure that could potentially cause massive hepatic infarction and subsequent sepsis with hepatic abscess, which can be a fatal complication. Here, we introduce a new transarterial technique that uses a hemostat with a stent graft, which successfully rescued a patient had suffered post‐PD bleeding. Abstract : This case demonstrated the successful treatment of a patient with post‐PD bleeding by transarterial stenting. Although sufficient experience and skill in angiographic techniques are required of is mandatory, and the need for a stent is largely determined by the arterial anatomy, we suggest that this technique may be promising for improving short‐term outcomes for post‐PD bleeding.